Aerobic and anaerobic test performance among elite male football players in different team positions - Nilsson, J.; Cardinale, D. (LASE Journal of Sport Science, 2015)
The purpose was to determine the magnitude of aerobic and anaerobic performance factors among elite male football players in different team positions. Thirty-nine players from the highest Swedish division classified as defenders (n=18), midfield players (n=12) or attackers (n=9) participated. Their mean (± sd) age, height and body mass (bm) were 24.4 (±4.7) years, 1.80 (±5.9)m and 79 (±7.6)kg, respectively. Running economy (RE) and anaerobic threshold (AT) was determined at 10, 12, 14, and 16km/h followed by tests of maximal oxygen uptake (VO2max). Maximal strength (1RM) and average power output (AP) was performed in squat lifting. Squat jump (SJ), counter-movement jump with free arm swing (CMJa), 45m maximal sprint and the Wingate test was performed. Average VO2max for the whole population (WP) was 57.0mL O2•kg-1min-1. The average AT occurred at about 84% of VO2max. 1RM per kg bm0.67 was 11.9±1.3kg. Average squat power in the whole population at 40% 1RM was 70±9.5W per kg bm0.67. SJ and CMJa were 38.6±3.8cm and 48.9±4.4cm, respectively. The average sprint time (45m) was 5.78± 0.16s. The AP in the Wingate test was 10.6±0.9W•kg-1. The average maximal oxygen uptake among players in the highest Swedish division was lower compared to international elite players but the Swedish players were better off concerning the anaerobic threshold and in the anaerobic tests. No significant differences were revealed between defenders, midfielders or attackers concerning the tested parameters presented above.